Comparative evaluation of the effectiveness of acellular dermal matrix allograft and subepithelial connective tissue to coronally advanced flap alone in the treatment of multiple gingival recessions: A clinical study - Pallavi Thakare; Vidya Baliga; Manohar Laxman Bhongade (Wolters Kluwer Medknow Publications, 2015)
Background: Obtaining predictable and esthetic root coverage has become an important part of periodontal therapy. Several techniques have been developed to achieve these goals with variable outcomes. The aim of this study was to appraise the effectiveness of acellular dermal matrix allograft (ADMA) and subepithelial connective tissue graft (SCTG) compared to coronally advanced flap (CAF) in the treatment of multiple gingival recessions. Materials and Methods: A total of 30 patients aged between 18 and 50 years, with multiple Miller's Class I and II recessions on labial or buccal surfaces of teeth were selected for this study. The patients were randomly assigned to CAF + ADMA, CAF + SCTG and CAF groups with 10 patients in each group. The clinical parameters assessed were probing pocket depth (PPD), clinical attachment level (CAL), gingival recession (GR), width of keratinized tissue, plaque index and papilla bleeding index at base line and 6 months after surgery. Results: Statistical analysis using One-way ANOVA suggested that the root coverage obtained was greater in the ADMA + CAF (89.83 ± 15.29%), when compared to SCTG + CAF (87.73 ± 17.63%) and CAF (63.77 ± 27.12%) groups. The predictability for coverage of> 90% was greater in CAF + ADMA (65%) when compared with SCTG + CAF (61.66%) and CAF (31.17%). Improvements in the clinical parameters from baseline were found in all the three groups treated. Conclusion: It was concluded that all three techniques could provide root coverage in Miller's class I and II gingival recessions; but greater % root coverage and predictability for coverage of> 90% could be expected with CAF + ADMA and CAF + SCTG groups when compared with CAF alone.